Validation of Indonesian Version of Offence-Related Feelings of Guilt and Shame: A Rasch Model Analysis - Salma Salma; Dian Veronika Sakti Kaloeti; Yohanis Franz La Kahija (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2022)
This study aims to conduct an adaptation and validation of the Offence-Related Feelings of Shame and Guilt Scale (ORSGS) in the Indonesian language. ORGS was translated into the Indonesian language using a forward translation method by a bilingual psychology expert. Five hundred ten male prisoners from three correctional institutions in Indonesia were recruited and completed the Indonesian version of ORSGS in paper-and-pencil. A Rasch model approach was applied to evaluate the psychometric properties and validity of the adapted scale. The results showed that the Indonesian version of ORSGS had moderate Cronbach’s Alpha reliability (α= .65) and excellent item reliability (.99). Item logit ranged from -1.08 to .72 with a separation value of 8.79, showing that items were grouped into 12 groups. The unidimensionality was found as acceptable/ moderate by 30.4% total variance explained from Principal Component Analysis but still needs further confirmatory analysis. Item 1 and 2 were found to be misfit and need to be evaluated. According to the Rasch model result, it can be concluded that the Indonesian version of ORSGS was valid (10 out of 12 items were fit) and reliable (Item reliability: .99) to be used in the prisoner population. However, further investigation about its multidimensionality and criterion validity still needs to be conducted